Rethinking the didactic-educational space: suggestions for promoting school inclusion - Michela Galdieri; Diana Carmela Di Gennaro (Firenze University Press, 2022)
The central role played by space within the educational field, considered as a prerequisite for action, redefines the didactic experience through the meanings of design and organization, implying a systemic relationship between teacher, learner and contexts. The aim of this paper is to reflect upon the meanings of space, spatiality, accessibility and the opportunity to prepare educational and didactic places in which the inclusion of each and every one can be promoted, including pupils with complex communication needs. Indeed, for those pupils the absence of language, a partial or not very functional use of language can represent a limitation to well-being, an obstacle to activity and an impediment to participation to school context.   Ripensare lo spazio didattico-educativo: suggestioni per promuovere l'inclusione scolastica. Il ruolo centrale dello spazio in ambito educativo, inteso come presupposto dell'azione, riconfigura l'esperienza didattica nei significati di progettazione e di organizzazione, implicando una relazione sistemica tra docente, discente e ambiente. L'obiettivo di questo lavoro è di riflettere sui significati di spazio, spazialità, accessibilità e sull'opportunità di predisporre luoghi dell'educazione e della didattica nei quali favorire l'inclusione di tutti e di ciascuno, ivi compresi, gli alunni con bisogni comunicativi complessi (BCC) nei quali l'assenza del linguaggio, un uso parziale o poco funzionale può costituire una limitazione al benessere, un ostacolo all'attività e un impedimento alla partecipazione nel contesto scolastico.